MTHFR gene rs1801133 +677C>T Exon4 Polymorphism in Susceptibility with Rheumatoid Arthritis in Najaf Population - Rashad Kadhim Mahmood Al-Akhras (Journal of Global Pharma Technology, 2016)
Background: The prevalence of Rheumatoid Arthritis (RA)   has been raised in Iraq. The medical costs of such increased prevalence are high. Global studies have revealed polymorphisms of MTHFR (Methylenetetrahydrofolate Reductase) gene to be associated with Rheumatoid Arthritis (RA). This polymorphism can cause changes in various metabolic variables. Methods: The current study consists of 100 RA patients and 100 healthy control individuals. Variable parameters data included Anti-Cyclic cytrulinated peptide expression (ACCP), Rheumatoid factor (RF), C - reactive protein (CRP) in serum and Erythrocytes sedimentation rate (ESR) levels. Genotyping of MTHFR gene polymorphism is carried out by RFLP-PCR. Various statistical analyses were applied to analyze the data. Results: The estimation of immunological and biochemical data pointed out significant differences in Gender, RF, ACCP, CRP, ESR and age in RA when compared with those of the control group. The genotyping results were found to be consistent with Hardy-Weinberg equilibrium. The analysis of the genotype distribution under various inheritance models highlighted significant differences in SNP of MTHFR gene polymorphism among RA patients when compared with the control group under the dominant homozygote, heterozygote and recessive homozygote. The genotype and allele frequencies of the MTHFR SNP rs1801133; highlighted significant rises of the risk of RA CT (P =0.0335), (OR=1.9409), (95%CI 1.0532-3.5766) when compared with control subjects. We found that the CT genotype is associated with the risk of RA comparing with CC and TT genotypes. Clinical characteristics were observed to change significantly with respect to the genotype distribution (risk factors) of the investigated SNP. Conclusion: MTHFR gene polymorphism (rs1801133) is implicated in the pathogenesis of Rheumatoid arthritis in Najaf population.Keywords: Rheumatoid arthritis, MTHFR, Rs1801133, RFLP-PCR, ACCP, CRP, RF.